2018
DOI: 10.1371/journal.pmed.1002531
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death and infant mortality rates among full-term births in the United States between 2010 and 2012: An observational study

Abstract: BackgroundWhile the high prevalence of preterm births and its impact on infant mortality in the US have been widely acknowledged, recent data suggest that even full-term births in the US face substantially higher mortality risks compared to European countries with low infant mortality rates. In this paper, we use the most recent birth records in the US to more closely analyze the primary causes underlying mortality rates among full-term births.Methods and findingsLinked birth and death records for the period 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 13 publications
3
27
0
1
Order By: Relevance
“…This is in agreement with Padmanabhan et al, 2019 [42] who found 77% of malformed babies were full-term. This is in agreement with Bairoliya, and Fink, 2018 [43] who found that CA represented about 58.1% of causes of full-term mortality in early neonatal period. This is in agreement with Fontoura and Cardoso, 2014 [44] who found higher prevalence of CA with full-term babies.…”
Section: Resultssupporting
confidence: 92%
“…This is in agreement with Padmanabhan et al, 2019 [42] who found 77% of malformed babies were full-term. This is in agreement with Bairoliya, and Fink, 2018 [43] who found that CA represented about 58.1% of causes of full-term mortality in early neonatal period. This is in agreement with Fontoura and Cardoso, 2014 [44] who found higher prevalence of CA with full-term babies.…”
Section: Resultssupporting
confidence: 92%
“…However, few studies have conducted a comprehensive investigation of the epidemiology of BDs with respect to the birth policy changes in China. BDs or congenital anomalies are defined as structural or functional anomalies occurring in a fetus or newborn and are the leading causes of infant death globally [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…15 While in poor countries, the most frequent causes of mortality in full term LB within the first seven days of life are obstetric infections, trauma and asphyxia, in middle-and high-income countries the main causes of mortality are sudden infant death syndrome and congenital malformations, including congenital heart defects. 17,18 In LB with greater Viability -this being a concept related to greater probability of existence outside the uterus, not limited to a few hours but potentially possible for months and even years, 19 mortality rates are associated with poor access to health care, which complicates the implementation of timely interventions in the period pre-and post-natal. 8 The mortality rate on the first day of life was higher among boys, infants from multiple pregnancies and those of indigenous ethnicity/skin color.…”
Section: Discussionmentioning
confidence: 99%